Sobre el Islam. - Antúnez Aldunate, Jaime (Humanitas (07172168))
The book "On Islam" by Rémi Brague, translated into Spanish by José Antonio Millán Alba and Blanca Millán García, analyzes Islamic culture in the Middle Ages and the difference between the Islamic religion and the civilization it engendered. Brague highlights the importance of the figure of Muhammad and the legal nature of Islam, as well as the tension between Islamophobes and defenders of dialogue with Islam. The author also addresses the issue of violence in the history of Islam and the interpretation of jihad as defensive in the present day.